Executive coaching with backbone and heart : - O’Neill, Mary Beth (Jossey-Bass Publishers, 2000)
If you've been looking for sound direction on how to coach top executives, here it is. In Executive Coaching with Backbone and Heart, Mary Beth O'Neill outlines the dynamic approach to coaching leaders that she's developed over the course of a twenty-year career. Her unique perspective and sage advice, backed by a specific four-phase methodology, gives you the means to successfully manage the coach-client relationship and effect dramatic changes that ensure the business outcomes leaders' want. It's a one-of-a-kind guide for executive coaches--both aspiring and established--that fills a long-standing gap in coaching literature.